(untitled) (Agro Productividad, 2024)
Objective: To obtain protocols for clonal micropropagation, crop planning, and in vitro conservation of Rhycholaelia digbyana (Lindley) Schltr. Methodology: The effects of the Kundson C basal medium and benzylaminopurine concentration were evaluated for clonal micropropagation. The treatment with the greatest number of shoots formed per apex was selected for crop planning. Experiments were conducted to determine the effect of basal medium Murashige and Skoog concentration at 2.2 gL-1 and 4.4 gL-1; sorbitol, mannitol, and sucrose at 1, 2, and 3% on slow growth. Results: The best treatment for clonal micropropagation and crop planning was identified as 21.60 gL-1 Knudson C with 8.80 µM benzylaminopurine. This treatment resulted in uniform-sized shoots produced. The multiplication process can yield 10,240 seedlings in 12 months. Slow growth was achieved using Murashige and Skoog basal media at 2.2 gL-1 with 1% mannitol. Implications: More experiments must be conducted to determine the best shoot induction conditions and improve resource efficiency. Conclusions: These findings represent the first report on micropropagation and ex-situ conservation to preserve germplasm for this species as an important resource for the floriculture industry.